Identifikasi Jenis Kalimat dalam Teks Prosa pada Buku Bahasa Indonesia Tingkat Lanjut Cakap Berbahasa dan Bersastra Indonesia Kelas XI Kurikulum Merdeka - Talitha Febiola; Anisah Ryan Putri Herlina; Rifqi Nandana Mahardika; Najmi Ali Mumtaz; Asep Purwo Yudi Utomo; Qurrota Ayu Neina (Jurnal Insan Pendidikan dan Sosial Humaniora, 2023)
This study focuses on the analysis of the study of sentence types in prose text literary works. The formulation of the problem in this study is how the arrangement or sentence structure is contained in the prose text of the Bahasa Indonesia Tingkat Lanjut Cakap Berbahasa dan Bersastra Indonesia Kelas XI Kurikulum Merdeka textbook. Prose text is a genre in literature which is commonly called fiction or narrative text. Prose texts presented in narrative form contain various types of sentences. Sentence types are divided into declarative sentences, interrogative sentences, imperative sentences, and exclamatory sentences. This research was conducted with the aim of finding and describing types of sentences based on syntactic structures in prose texts of the Bahasa Indonesia Tingkat Lanjut Cakap Berbahasa dan Bersastra Indonesia Kelas XI Kurikulum Merdeka textbook. The method used in this study is a descriptive qualitative approach combined with note-taking techniques for the data collection process and syntax analysis techniques. Qualitative research is included in the methodology used for research procedures that produce descriptive data. Based on the analysis that has been carried out on prose texts, it is known that of the 3 prose titles analyzed, namely “Penggali Sumur yang Ingin Pensiun”, “Saat Ayah Meninggal Dunia”, and “Janji Ayah” there are only three types of sentences, namely 229 declarative sentences, 17 question sentence, and 1 imperative sentence. So, it can be concluded that there are no exclamatory sentences in the prose text but are strongly influenced by declarative sentences.